Specific Preferences in Lineage Choice and Phenotypic Plasticity of Glioma Stem Cells Under BMP4 and Noggin Influence - Videla Richardson, Guillermo Agustín (2015)
Although BMP4-induced differentiation of glioma stem cells (GSCs) is well recognized, details of the cellular responses triggered by this morphogen are still poorly defined. In this study, we established several GSC-enriched cell lines (GSC-ECLs) from high-grade gliomas. The expansion of these cells as adherent monolayers, and not as floating neurospheres, enabled a thorough study of the phenotypic changes that occurred during their differentiation. Herein, we evaluated GSC-ECLs' behavior toward differentiating conditions by depriving them of growth factors and/or by adding BMP4 at different concentrations. After analyzing cellular morphology, proliferation and lineage marker expression, we determined that GSC-ECLs have distinct preferences in lineage choice, where some of them showed an astrocyte fate commitment and others a neuronal one. We found that this election seems to be dictated by the expression pattern of BMP signaling components present in each GSC-ECL. Additionally, treatment of GSC-ECLs with the BMP antagonist, Noggin, also led to evident phenotypic changes. Interestingly, under certain conditions, some GSC-ECLs adopted an unexpected smooth muscle-like phenotype. As a whole, our findings illustrate the wide differentiation potential of GSCs, highlighting their molecular complexity and paving a way to facilitate personalized differentiating therapies.